The effect of methods contraception during the transition to adulthood among young people in Chiapas. - Avila Sánchez, María de Jesús; Jáuregui Díaz, José Alfredo (2015)
The main objective of this study is to advance the understanding of transitions to adulthood among young people in Chiapas and its relationship with contraceptive use at first intercourse. Distinguishing by gender, ethnicity and context of residence. The analysis is based on young people born between 1981 and 1998, and merely observes the transition to the first binding partner and first child (a) to 29 years old, with the source of information ENJ2010. Analysis was applied event history, event history analysis. Life table model were calculated and Cox proportional hazards were developed. The results show that young people who belong to the younger cohorts are postponing the start of married life and the birth of the first child (a) compared to older youth. In addition, as expected is confirmed that the use of contraception at first intercourse is associated with a lower risk to join a couple and their first child (a).